2011
DOI: 10.1002/asl.351
|View full text |Cite
|
Sign up to set email alerts
|

Climate response to aerosol injection at different stratospheric locations

Abstract: The effect of altitude and latitude of sulfate aerosol injection into the stratosphere on climate is studied with Earth system model INMCM. The model includes the general circulation of the atmosphere and oceans as well as a sulfate aerosol component, and is used to determine the most effective injection scenario for reducing changes in temperature and precipitation at a global level and in the Arctic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…This is consistent with Volodin et al (2011) who found increased land-sea cooling contrast in annual mean temperature using the INMCM model forced with 4 Mt S/year equatorial stratospheric aerosol injection. The land-sea cooling contrast is larger for TXx than TNn (Fig 4d, e; Table 3), consistent with the stronger relationship of shortwave forcing to TXx.…”
Section: Spatial Response In Extremessupporting
confidence: 92%
“…This is consistent with Volodin et al (2011) who found increased land-sea cooling contrast in annual mean temperature using the INMCM model forced with 4 Mt S/year equatorial stratospheric aerosol injection. The land-sea cooling contrast is larger for TXx than TNn (Fig 4d, e; Table 3), consistent with the stronger relationship of shortwave forcing to TXx.…”
Section: Spatial Response In Extremessupporting
confidence: 92%
“…Модель была дополнена блоком, описывающим цикл стратосферного сульфатного аэрозоля (Volodin et al, 2011). Данный блок учитывает процесс химической трансформации предшественников аэрозоля в аэрозольные частицы, а также физические процессы переноса  диффузии, гравитационного оседания и вымывания аэрозольных частиц осадками в тропосфере (Рябошапко, 2011; Володин и др., 2011).…”
Section: математическая модель климатических изменений в арктикеunclassified
“…H 2 S was injected at the height of 22-24 km in the latitudinal zone of 10 • S-10 • N. It was done homogeneously in the selected volume with constant intensity during calendar year. It was shown previously that injections at such heights and latitudinal zone provide maximum effect (Volodin et al, 2011).…”
Section: Description Of the Model And External Parametersmentioning
confidence: 99%
“…Total emissions in equivalent of CO 2 for both scenarios (RCP8.5 and A1FI) are almost identical. Thus, we can assume that the results obtained in this study will be consistent with the results of previous studies based on the scenario A1FI (Volodin et al, 2011).…”
Section: Description Of the Model And External Parametersmentioning
confidence: 99%